Introduction to Curriculum Development and Medical Education Scholarship for Resident Trainees: A Webinar Series - Shannon K. Martin; James Ahn; Jeanne M. Farnan; H. Barrett Fromme (Association of American Medical Colleges, 2016)
Abstract Introduction A common career aspiration among residents is to become a clinician-educator, though standard postgraduate training may not prepare trainees for the academic and scholarly requirements of this career. To address this need, we designed and implemented an asynchronous, interactive webinar series detailing a systematic approach to medical education research and scholarship. The series was piloted as part of a new track at the University of Chicago for residents interested in additional training and completing an educational learning project in medical education. Methods We aimed to use this series to introduce relevant frameworks in curriculum development, program evaluation, and learning theory. Materials associated with this publication include six webinars and corresponding summary reference handouts, discussion assignments, and answer keys. Additional materials include a faculty course director packet and sample feedback for discussion assignments. Each webinar is an 8- to 20-minute narrated presentation with goals and objectives, an overview of each session's content, and example vignettes. Residents viewed presentations and completed a two-part discussion assignment for each webinar, which included reflection on the educational material and vignettes, faculty feedback on this reflection, and application of webinar material and faculty feedback to their own experiences in medical education. Results All residents in the pilot completed the webinars and assignments. Residents' reactions to the webinar series have been positive, and residents have commented that self-paced learning with directed faculty feedback is a desirable instructional method for this material. Discussion This series is well suited to introduce fundamental concepts in medical education scholarship and inspire self-directed study for motivated learners.